Antimicrobial and conducting polymer substrate derived from hybrid structures of silver nanoparticles and multiwall carbon nanotubes. (February 2014) - Kumar, S.; Pawar, S. P.; Chatterjee, K.; Bose, S.
Abstract : Hybrid nanocomposites of polycaprolactone (PCL) with multiwall carbon nanotubes (MWNTs) and silver nanoparticles (nAg) were prepared by melt mixing. Synergetic effect of the two nanofillers (MWNT and nAg) in PCL matrix was evaluated for dielectric and antibacterial properties. Dielectric results showed that the addition of nAg as filler in PCL matrix (PCL/nAg) had no effect on conductivity, whereas addition of MWNT in PCL matrix (PCL/MWNT) caused a sharp increase in conductivity of PCL. Interestingly, the hybrid nanocomposite (PCL/MWNT/nAg) incorporating MWNT and nAg also exhibited high electrical conductivity. The hybrid composite was found to have antibacterial property similar to that of PCL/nAg composite for lower loading of nAg. This study demonstrates that the synergetic interaction of the nanofillers in the hybrid nanocomposite improves both electrical conductivity and antibacterial properties of PCL.